(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
This research is immersed in the analysis of contemporary dynamics that generate the processes of reconfi guration of rurality in a territorial sense, the relationship of the community with the environment or environment and its effects on the rural culture, based on the resignifi cation assigned by rural families in Jesús Tepactepec. Among the purposes is the purpose of deepen the way in which the territory is taken, from the physical, to the symbolic confi guration in the inhabitants and the influence on the reproduction of the rural way of life, for this, it is investigated in the transformations within rural territory and in the reproduction of the culture of the settlers, which allows an exploration in the relations between society and nature and human beings and environment, through the ways in which the population perceives, coexists and confronts pollution of the Zahuapan River, by the present dynamics of activities industrial and its effect on the concentration of populations.